The Role of Locus of Control in Education, Occupation, Income and Healthy Habits: Evidence from Australian Twins - Sen Xue; Michael P. Kidd; Anh T. Le; Kathy Kirk; Nicholas G. Martin (Global Labor Organization (GLO), 2019)
The role of non-cognitive skills in socio-economic behavior is a burgeoning research area in economics. Much interest is focused on the personality trait, locus of control, a measure of the extent to which individuals believe their fate is self-determined. The existing empirical literature generally estimates the role of locus of control via OLS. The legitimacy of the approach relies upon stability of locus of control as well as the correct specification of the model, i.e. no omitted variable bias. Recent evidence is supportive of treating locus of control as predetermined, particularly for working age individuals. However, the behavioural genetics consensus is that personality traits including locus of control have a significant heritability component. This suggests the potential for omitted variable problems associated with the prior literature's attempt to identify the impact of locus of control using cross-sectional methods. We address the issue of omitted shared family background and genetic factors using data on both monozygotic and dizygotic twins to examine the role of locus of control. Comparison of results across OLS and twins fixed effect estimators is consistent with substantial upward bias in previous estimates of the locus of the control due to omitted variable problems.
Keywords: J24; J21; J31; 330; Locus of control; twin studies; socioeconomic outcomes